Video Threads: Asynchronous Video Sharing for Temporally Distributed Teams - Barksdale, Jeremy T.; Inkpen, Kori; Czerwinski, Mary; Hoff, Aaron; Johns, Paul; Roseway, Asta; Venolia, Gina (CSCW 2012, 2012)
Work teams are often geographically distributed, and in some cases, experience large time-zone differences with no overlap in working hours. We explored the use of asynchronous video in temporally distributed teams. We developed VideoThreads, which provides a novel thread-based visualization of video messages. Based on a deployment to four teams, we offer design recommendations and insights about the benefits of asynchronous video sharing.